Lipidomic traits of plasma and cerebrospinal fluid in amyotrophic lateral sclerosis correlate with disease progression. Issue 3 (26th June 2021) - Sol, Joaquim; Jové, Mariona; Povedano, Monica; Sproviero, William; Domínguez, Raul; Piñol-Ripoll, Gerard; Romero-Guevara, Ricardo; Hye, Abdul; Al-Chalabi, Ammar; Torres, Pascual; Andres-Benito, Pol; Area-Gómez, Estela; et al.
Abstract: Since amyotrophic lateral sclerosis cases exhibit significant heterogeneity, we aim to investigate the association of lipid composition of plasma and CSF with amyotrophic lateral sclerosis diagnosis, its progression and clinical characteristics. Lipidome analyses would help to stratify patients on a molecular basis. For this reason, we have analysed the lipid composition of paired plasma and CSF samples from amyotrophic lateral sclerosis cases and age-matched non-amyotrophic lateral sclerosis individuals (controls) by comprehensive liquid chromatography coupled to mass spectrometry. The concentrations of neurofilament light chain—an index of neuronal damage—were also quantified in CSF samples and plasma. Amyotrophic lateral sclerosis versus control comparison, in a moderate stringency mode, showed that plasma from cases contains more differential lipids ( n  = 122 for raw P  < 0.05; n  = 27 for P  < 0.01) than CSF ( n  = 17 for raw P  < 0.05; n  = 4 for P  < 0.01), with almost no overlapping differential species, mainly characterized by an increased content of triacylglyceride species in plasma and decreased in CSF. Of note, false discovery rate correction indicated that one of the CSF lipids (monoacylglycerol 18:0) had high statistic robustness (false discovery rate- P  < 0.01). Plasma lipidomes also varied significantly with the main involvement at onset (bulbar, spinal or respiratory). Notably, faster progression cases showed particular lipidome fingerprints, featured by decreased triacylclycerides and specific phospholipids in plasma, with 11 lipids with false discovery rate- P  < 0.1 ( n  = 56 lipids in plasma for raw P  < 0.01). Lipid species associated with progression rate clustered in a relatively low number of metabolic pathways, mainly triacylglyceride metabolism and glycerophospholipid and sphingolipid biosynthesis. A specific triacylglyceride (68:12), correlated with neurofilament content ( r  = 0.8, P  < 0.008). Thus, the present findings suggest that systemic hypermetabolism—potentially sustained by increased triacylglyceride content—and CNS alterations of specific lipid pathways could be associated as modifiers of disease progression. Furthermore, these results confirm biochemical lipid heterogeneity in amyotrophic lateral sclerosis with different presentations and progression, suggesting the use of specific lipid species as potential disease classifiers. Abstract : Sol et al. report that in case–control approaches, plasma lipidomic profile is richer in differences than CSF. Interestingly, patients with faster progression show decreased plasmatic triacylglycerides and phospholipids, compatible with hypermetabolism. They conclude that the plasma lipidomic profile holds promise for patient stratification. Graphical Abstract: